EVALUASI KINERJA BATERAI BERUSIA 10 TAHUN MENGGUNAKAN DATA PENGUKURAN DI GARDU INDUK 150 KV JEPARA - Ahmad Shofa; Muhammad Rizky Adi (Khamdan Karya Cipta, 2025)
Batteries serve as a crucial backup direct current (DC) source in substations, especially during power outages (blackouts). The reliability and lifespan of these batteries are critical factors in ensuring the continuous operation of the system. This study analyzes the performance of 110 VDC NiCd (Nickel-Cadmium) alkaline batteries at the Jepara 150 kV Substation, which have been in operation for over 10 years. This research is relevant given that the replacement criteria for substation batteries typically range from 10-15 years. This study employs a comparative method using discharging data collected in 2018 and 2020. The results show that while the battery's efficiency remains stable at 99.41%—which is still considered good and above the standard (>80%)—several key parameters have degraded. The battery is still capable of supplying the load for 16.9 hours. However, its specific gravity value has decreased to 1.1305 kg/l, which is below the standard (1.17-1.19 kg/l). Furthermore, the total battery voltage in 2020 was measured at 85.8 V, a drop of 2.1 V from 2018. Further analysis found that this voltage drop was caused by the presence of